Prevalence of dysmenorrhea and intention to seek care among in-school adolescents in Nigeria: a cross-sectional study - Fehintola, Funmito O.; Olaleke, Temitayo A.; E. Joshua, Oluwatobi; Adelagun, Adeyinka O.; Aremu, Oluwatobi; Solomon, Busola B.; Olowookere, Samuel A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Dysmenorrhea is a problem that girls face and often manage themselves with or without support from health professionals. The objective of this study was to assess the prevalence of dysmenorrhea and intentions to seek care among in-school adolescents. Methods: Descriptive cross-sectional research design was utilized, and a two stage sampling technique was used in selecting 315 participants based on the required sample size. Data were analyzed using SPSS version 20, and results were summarized using descriptive and inferential statistics with level of significance set at p<0.05. Results: The mean age of respondents was 15.49±1.44 years. Dysmenorrhea was prevalent among 80% of the respondents. Predictors of intention to seek care for dysmenorrhea among the respondents were awareness about health services for dysmenorrhea (AOR=2.15, 95%CI=1.19-3.86, p=0.012), cost of care for dysmenorrhea (AOR=0.29, 95%CI=0.12-0.62, p=0.002), and perception on dysmenorrhea (AOR=0.21, 95%CI=0.10-0.40, p=0.001). Conclusions: Dysmenorrhoea is a common health problem among in-school adolescents in Nigeria. Health education campaigns should be organized to create awareness on availability of services for treatment of dysmenorrhea and correct the misconception that dysmenorrhea needs no care especially in situations where the pain is moderate to severe.